Introducing Bangladeshi writing in English: emergence to the present - Quayum, Mohammad Abdul; Hasan, Md. Mahmudul (IIUM Press, International Islamic University Malaysia, 2018)
In postcolonial literary criticism, Bangladeshi writing in English has not received the scholarly attention or the recognition it deserves. However, there is an irony here because colonial Bengal was perhaps the first among the British colonies to embrace English education and its people had early working experiences with the British. Moreover, this literary tradition claims some of the earliest writers of literature written in English outside the British and American canons. In the present time, it has gained renewed vibrancy as writers both in Bangladesh and in the diaspora, especially in the UK, have produced English works both in the original and in translation. Considering the rich background, sophistication and huge potential of Bangladeshi writing in English, in this article we will provide a historical overview and the varying strands of this literary tradition. As editors of this special journal issue, we will also attempt a general outline of the articles included in it and consider the main themes they explicate.